Prevalence of Endometriosis During Abdominal or Laparoscopic Hysterectomy for Chronic Pelvic Pain. Issue 6 (June 2016) - Mowers, Erika L.; Lim, Courtney S.; Skinner, Bethany; Mahnert, Nichole; Kamdar, Neil; Morgan, Daniel M.; As-Sanie, Sawsan
Abstract : OBJECTIVE: To estimate the prevalence of surgically confirmed endometriosis in women undergoing laparoscopic or abdominal hysterectomy, including those with and without preoperative indications of chronic pelvic pain or endometriosis, and to describe characteristics and operative findings associated with surgically confirmed endometriosis in women undergoing hysterectomy for chronic pelvic pain. METHODS: A retrospective cohort study was performed with 9, 622 women who underwent laparoscopic or abdominal hysterectomy for benign indications in the Michigan Surgical Quality Collaborative from January 1, 2013, to July 2, 2014. The prevalence of surgically confirmed endometriosis, determined by review of the operative report and surgical pathology, was calculated for the entire cohort and for subgroups of women with and without chronic pelvic pain or endometriosis. Multivariate logistic regression models were used to identify characteristics associated with surgically confirmed endometriosis at the time of hysterectomy among women with chronic pelvic pain. RESULTS: Of the 9, 622 hysterectomies available for analysis during the study period, 15.2% (n=1, 465) had endometriosis at the time of hysterectomy. Among the 3, 768 women with a preoperative indication of chronic pelvic pain, fewer than one in four had endometriosis (806/3, 768 [21.4%]). Even among those with preoperative indication of endometriosis, many women did not actually have endometriosis at the time of hysterectomy (527/1, 232 [42.8%]). The rate of unexpected endometriosis in women without a preoperative indication of chronic pelvic pain or endometriosis was 8.0% (434/5, 457). Among women with a preoperative indication of chronic pelvic pain (n=3, 786), multivariate analysis showed endometriosis was more common in women of younger age, white race, lower body mass index, and those who failed another treatment previously. Among those with pelvic pain, oophorectomy was more commonly performed in women with surgically confirmed endometriosis than those without (47.4% compared with 33.3%, P <.001). CONCLUSION: Fewer than 25% of women undergoing laparoscopic or abdominal hysterectomy for chronic pelvic pain have endometriosis at the time of surgery. Abstract : Endometriosis is found in fewer than one fourth of women undergoing laparoscopic or abdominal hysterectomy for chronic pelvic pain.